2016
DOI: 10.1177/0193945915625065
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Religiosity in Adolescents Living With Sickle Cell Disease

Abstract: This study purports to address paucity in the literature regarding how adolescents with sickle cell disease (SCD) describe and experience spirituality and religiosity (S/R). This was a qualitative descriptive study. Two semi-structured interviews were conducted with nine adolescents ( Mage = 16.2 years). Data were analyzed using a template analysis style and a concurrent analysis process of data reduction. Three major themes encompassed the participants’ descriptions of the relationships between S/R, health an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…Cook's (2000) study of the resilience of inner-city minority youth found that religious youth had greater psychological well-being than the control group because the church provided teens with the three levels of support-mentorship, community support, and a relationship with God. All three components of support also appeared in three other studies (Clayton-Jones, Haglund, Belknap, Schaefer, & Thompson, 2016;Liu, Carter, Boehm, Annandale, & Taylor, 2014;Nourian, Shahbolaghi, Tabrizi, Rassouli, & Biglarrian, 2016). However, given that most often church leader and community support were the only types of support mentioned (11 out of 18 studies), we coded God support as Spiritual (specifically Theistic Spirituality) and support in religious communities as RS Support.…”
Section: (Q8) How Do Youth Experience Their Religiosity and Spiritualmentioning
confidence: 99%
See 2 more Smart Citations
“…Cook's (2000) study of the resilience of inner-city minority youth found that religious youth had greater psychological well-being than the control group because the church provided teens with the three levels of support-mentorship, community support, and a relationship with God. All three components of support also appeared in three other studies (Clayton-Jones, Haglund, Belknap, Schaefer, & Thompson, 2016;Liu, Carter, Boehm, Annandale, & Taylor, 2014;Nourian, Shahbolaghi, Tabrizi, Rassouli, & Biglarrian, 2016). However, given that most often church leader and community support were the only types of support mentioned (11 out of 18 studies), we coded God support as Spiritual (specifically Theistic Spirituality) and support in religious communities as RS Support.…”
Section: (Q8) How Do Youth Experience Their Religiosity and Spiritualmentioning
confidence: 99%
“…Second, RS Belief was another process of influence frequently identified in Qualitative studies. Teens often felt that religion gave them a sense of belonging (e.g., Benavides, 2012), scriptures provided them with important values and directions for life (e.g., Clayton-Jones et al, 2016), and that God was a trusted source of protection, strength, comfort, and guidance (e.g., Hills, Meyer-Weitz, & Asante, 2016;Liu et al, 2014;Van der Meer Sanchez, De Oliveira, & Nappo, 2008). These themes have largely been ignored by quantitative researchers.…”
Section: (Q8) How Do Youth Experience Their Religiosity and Spiritualmentioning
confidence: 99%
See 1 more Smart Citation
“…In one qualitative study, adolescents described using spirituality through their connection with people (e.g. family, friends, and spiritual leaders), nature, and creative activities as a way of coping with painful crises or illness (Clayton-Jones et al, 2016). Additional coping strategies identified were helping others through volunteering activities and the use of humour, particularly about painful crises (Atoui et al, 2015;Clayton-Jones et al, 2016).…”
Section: Emotional Wellbeing and Copingmentioning
confidence: 99%
“…Religious beliefs and practices appear to help some adolescents find peace, strength, and comfort, especially during illness or painful crises as well as extending their social support network (Atoui et al, 2015;Clayton-Jones et al, 2016). However, their beliefs could be challenged at times when they felt overwhelmed by SCD or when they reflected on the fairness of having the condition.…”
Section: Emotional Wellbeing and Copingmentioning
confidence: 99%